VISUAL 3D PLANOGRAM MEMPERMUDAH PEMASANGAN MATERIAL PROMOSI HANDPHONE - Andik Prakasa Hadi; Fandy Achmad Faizal (STEKOM PRESS, 2020)
Smartphone retail sales in Indonesia are currently growing very rapidly. Point of Sales Material (POSM) is used to provide information about products to consumers, using displays to stimulate impulsive buying behavior. This study designed a 3D planogram visual media, which can visualize real-time with text, images, and videos. Media that has been developed by researchers is in the very good category with a percentage of 78% for the promoter segment that is more than 1 year and 77% for the new promoter segment who has worked at Samsung retail for less than 1 year. From the results of experalidation and user validation, for the aspect of video visualization and the 3D planogram module that has been developed, the category average AB score is 81-85. The display arrangement process can be done more quickly and precisely because the understanding of the planogram increases.